Proteases and their receptors in inflammation - Vergnolle, Nathalie; Chignard, Michel; SpringerLink (Online service). (Basel Springer, 2011)
Proteases are everywhere from prokaryotes to eukaryotes, from virus to bacteria and in all human tissues, playing a role in many biological functions. Among these functions, the inflammatory reaction is of particular interest. In inflamed tissues, proteases can have a microbial and/or host origin and are involved not only in tissue remodeling, but also in specific signaling to resident or inflammatory cells, thereby contributing to the innate immune response. This volume presents all advances in our knowledge of the role proteases and their inhibitors play in various diseases associated with inflammatory response. Mechanisms involved in protease signaling to cells are presented, and the different types of proteases that are present at inflammatory sites and their effects on the course of inflammation are discussed. Finally, the evidence for considering proteases and their receptors as potential molecular targets for therapeutic interventions in the treatment of inflammatory diseases is discussed in the context of specific organ inflammatory pathologies (the lung, gastrointestinal tract, skin, joints, etc.).
Proteolytic Enzymes and Cell Signaling: Pharmacological Lessons -- Serine and Cysteine Proteases and Their Inhibitors as Antimicrobial Agents and Immune Modulators -- Kallikrein Protease Involvement in Skin Pathologies Supports a New View of the Origin of Inflamed Itchy Skin -- Proteases from Inflammatory Cells: Regulation of Inflammatory Response -- Matrix Metalloproteinase Inhibitors as New Anti-inflammatory Drugs -- Dual Role for Proteases in Lung Inflammation -- Proteases and Fibrosis -- Proteases/Antiproteases in Inflammatory Bowel Diseases -- Proteinase-Activated Receptors and Arthritis -- Proteases, Coagulation, and Inflammation -- Proteases and Inflammatory Pain -- Microbial Proteases: Relevance to the Inflammatory Response -- Terminating Protease Receptor Signaling.
Electronic reproduction.
Keywords: Inflammation -- Mediators; Proteolytic enzymes; Electronic books